ETHICS AND THE BODY: THE ARTISTIC REPRESENTATION OF COGNITIVE PLASTICITY IN MARKO CHEREMSHYNA’S SHORT STORIES - Soletskyi, Oleksandr (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Objective. The article examines the features of artistic representation of cognitive plasticity in Marko Cheremshyna’s texts, reflecting on the representation of the iconotrope “body” as a cultural phenomenon, a mediator, and a retransmitter of ancient behavioral patterns and ethical postulates. Based on the study of the writer’s autobiography, contemporaries’ memories of him, and selected short stories, generalizations about the relationship between the “ethical” and the “corporeal” as a synthesized phenomenon of cognitive plasticity are formed, reflecting the synergetic process of identity formation. Research methodology. The study utilizes a system of hermeneutic, structural, and phenomenological methods. The author draws on the scientific methodology of semiotics, psychoanalysis, and employs the methodology of cognitive literary studies. This is determined by the specifics of the study, its object, and subject. Results. The body as an iconotrope in Marko Cheremshyna’s works serves as a form for differentiating generalizations about the external and internal, explicit and implicit, and in general, as an initial form for constructing contrasts of semantic flickers or existential dependencies in many texts. In the short story “Karby,” the author repeatedly notes dissonant cognitive reactions that are symbolically engraved through somatic loci. The body acts as a liminal zone of excitation and transformation, unfolding and dispersing, a kind of coexistence at the boundary, which forms the foundations of the soul’s world.